ANALISIS FAKTOR – FAKTOR YANG MEMPENGARUHI PENDAPATAN PEDAGANG KAKI LIMA DI KABUPATEN BELU - Hawu Haba, Betsyeba Ariyani; Ndoen, Wehelmina M; Neno, Marianus S; Foenay, Christien C (GLORY Jurnal Ekonomi dan Ilmu Sosial, 2023)
This study aiams to describe the income of street vendors in Belu district and to analyze the effect of working capital, working hours, age of traders, length of business and labor on the income of street vendors in Belu district. This type of research is a survey. Research with a quantitative descriptive approach, the variabels used include working capital, working hours , age of traders, length of labor, and income. The tape of data used is quantitative data with primary data sources. The data collection techniques used are interview, questionaires and technical observations. Descriptive and multiple linear regression analysis. Based on the results of the study, it shows that the working capital variable has a positive and significant effect on income, while the variable working hours, age of traders, length of business and labor, has no effect on the income of street vendors in Belu Regency. Keywords : Working Capital, Working hours, Age trader, Old business, Labor, Income, Street vendors.